1996
DOI: 10.1017/s0950268800058957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of influenza and respiratory syncytial virus on mortality in England and Wales from January 1975 to December 1990

Abstract: SUMMARYThe effects of influenza A and B and RSV on mortality in England and Wales were assessed by regression analysis for the period 1975-90. Morbidity data from sentinel practices were used to calculate 4-weekly rates of aggregated upper respiratory tract infections (URTI); PHLS laboratory reports were used as indices of infection, and 4-weekly death rates from all causes, excluding childbirths, were used to study relationships with mortality. Deaths correlated strongly with influenza A and B reports, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 24 publications
6
113
1
2
Order By: Relevance
“…Co-circulation of other respiratory viruses during influenza season, in particular the respiratory syncytial virus (RSV) [13], makes it challenging to estimate the influenza-associated burden indirectly. Several studies suggested that RSV is responsible for considerable morbidity and even mortality not only in children but also among older adults [2,[14][15][16]. Over the last 10 yrs the development of vaccines against RSV has progressed [17], and although a vaccine is not expected in the very near future, insight into the RSV-associated healthcare burden would be valuable.…”
mentioning
confidence: 99%
“…Co-circulation of other respiratory viruses during influenza season, in particular the respiratory syncytial virus (RSV) [13], makes it challenging to estimate the influenza-associated burden indirectly. Several studies suggested that RSV is responsible for considerable morbidity and even mortality not only in children but also among older adults [2,[14][15][16]. Over the last 10 yrs the development of vaccines against RSV has progressed [17], and although a vaccine is not expected in the very near future, insight into the RSV-associated healthcare burden would be valuable.…”
mentioning
confidence: 99%
“…RSV and PIV-3 infections recur throughout life despite the presence of specific neutralizing antibodies. There are annual epidemics of these virus infections in the community; in England and Wales, PIV-3 infections occur between May and September each year (16) and RSV infections occur every winter (23).…”
mentioning
confidence: 99%
“…In countries with a temperate climate, epidemics occur mainly in the winter, although they can begin in the fall and extend into early spring. [4][5][6][7][8][9] In southern Brazil, which has a predominantly temperate climate, RSV also produces epidemics in the winter months (June, July, and August) (Straliotto SM, unpublished data). However, the seasonality of RSV in the city of Rio de Janeiro, located in southeastern Brazil, occurs in the fall and early winter, thus preceding the outbreak in southern Brazil.…”
mentioning
confidence: 99%